2018
DOI: 10.1016/j.ultsonch.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the inertial cavitation threshold under multi-frequency ultrasound

Abstract: Through the introduction of multi-frequency sonication in High Intensity Focused Ultrasound (HIFU), enhancement of efficiency has been noted in several applications including thrombolysis, tissue ablation, sonochemistry, and sonoluminescence. One key experimental observation is that multi-frequency ultrasound can help lower the inertial cavitation threshold, thereby improving the power efficiency. However, this has not been well corroborated by the theory. In this paper, a numerical investigation on the inerti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 44 publications
3
43
0
2
Order By: Relevance
“…There have been an increasing number of studies that reported better results by combining multiple frequencies as opposed to using a single operating frequency [28] , [29] . These findings were further supported by higher cavitation signal measurements found in dual-frequency systems [30] , [31] as well as theoretical studies using simulations of bubbles dynamics [32] , [33] . As research began to focus on the potential of multi-frequency ultrasound in many applications [34] , [35] , [36] , the design of multi-frequency sonoreactors gained interests in recent times.…”
Section: Introductionsupporting
confidence: 75%
“…There have been an increasing number of studies that reported better results by combining multiple frequencies as opposed to using a single operating frequency [28] , [29] . These findings were further supported by higher cavitation signal measurements found in dual-frequency systems [30] , [31] as well as theoretical studies using simulations of bubbles dynamics [32] , [33] . As research began to focus on the potential of multi-frequency ultrasound in many applications [34] , [35] , [36] , the design of multi-frequency sonoreactors gained interests in recent times.…”
Section: Introductionsupporting
confidence: 75%
“…Dual-frequency HIFU can effectively activate the phase transition of PFP into microbubbles, significantly reducing the thermal damage threshold of HIFU, enhancing its antitumor efficacy, and realizing ultrasound monitoring imaging. The potential mechanism of dual-frequency-HIFU-enhanced cavitation could be related with bubble dynamics [23]. A dual-frequency approach displays more resonances termed as "combination resonances" and could promote the acoustical scattering cross-section significantly within a much wider range of bubble sizes due to the generation of more resonances [32].…”
Section: Discussionmentioning
confidence: 99%
“…The gas bubble could either oscillate stably or expand gradually and eventually collapse (stable and inertial cavitation). Cavitation could lead to thermal effects as well as chemical and optical effects [23]. Cavitation-enhanced anti-tumor efficacy mainly results from the enhanced thermal effects and mechanical/chemical effects of cavitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades, many theories emerged to explain the influence of multiple excitation frequencies, for example, more active zones are generated in the sonochemical reactor [55] , [56] due to the better pattern of the acoustic waves. Others reported the increase of nuclei generated in the bubble cluster [57] , [54] , increased mass transfer via micromixing [58] , the increase of collapse-strength [51] , [59] , [60] , [34] or the lowering of cavitational threshold [61] , [62] . The combination and simultaneous resonance properties of dual-frequency driving can also explain the increased collapse strength [63] .…”
Section: Introductionmentioning
confidence: 99%